Analisis Perbandingan Kompresi Half Byte ddan Byte Pair Encoding Pada File Bynari Atau Teks - Dedek Prasetyo; Tommy; Rizko Liza (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
A text file is a file that contains information in text form. Data derived from word processing documents, numbers used in calculations, names and addresses in the database are examples of text data input consisting of characters, numbers and punctuation marks. The process of sending messages or texts has now become a necessity for everyone through various media platforms that exist as a form of visual message. The large size of the text transmission of course sometimes becomes an obstacle, not to mention bandwidth is also a problem for users in the sending process. One solution to solve this problem is to use compression or compression techniques. Data compression is a method that supports technology in the use of networks for data transmission, data access, and data use. Some of the many compression algorithms that are declared good to be applied to text-based data compression are Byte Pair and Half Byte. The Half-Byte Algorithm takes advantage of the four left-hand bits which are often the same in sequence, especially in text files. Byte Pair Encoding Algorithm is a simple text compression algorithm based on pattern substitution. Both of these algorithms mandate the similarity of data as a compression process using a program that has been created with the Visual Basic 2010 programming language. Visual Basic 2010 is an OOP-based programming language or object oriented programming that utilizes .NET technology which is used to create applications in a work environment based on Windows. Visual Basic 2010 or Visual Basic . Comparative analysis will be carried out based on the results of compression, ratio, and processing time in determining which algorithm is more optimal.